STUDI EKSPERIMENTAL PERAN BACKGROUND MUSIC TERHADAP APPROACH BEHAVIOR : MODERASI CO-CREATION DAN MEDIASI PERCEIVED MOOD PADA KONSUMEN RUMAH ICE CREAM BARATAJAYA SURABAYA - Yovita Christiani; Dudi Anandya; Silvia Margaretha (Perpustakaan Universitas Surabaya, 2018)
This study aims to determine and analyze the role of background music on approach behavior, with the role of moderation co-creation and mediation perceived mood at consumers of Rumah Ice Cream Baratajaya Surabaya. Data processing is done by using SPSS 22 software. Data obtained from two different places, namely private universities in Surabaya and at Rumah Ice Cream Baratajaya Surabaya. The number of participants in this study were 160 respondents.The results of this study indicate that perceived mood proved to positively mediate the relationship between congruence of background music and approach behavior on consumers of Rumah Ice Cream Baratajaya Surabaya, co-creation proved to moderate the negative effect of congruence of background music on perceived mood at consumers of Rumah Ice Cream Baratajaya Surabaya.